Pengaruh Perubahan Suhu Terhadap Tegangan Tembus Pada Bahan Isolasi Cair - Alfian Junaidi (Faculty of Industrial Technology Universitas Islam Indonesia, 2008)
Lubricant oil is used to lubricate machines especially gasoline machine. To have ahighs performance lubricant oil, additive agent is added. Additive agent used for anti oxidant, anti rust of time worn, and anti foam. This research want to know the influence of temperature change on tension penetrate of lubricant oil. The sample use are lubricant oil SAE 40 and transformator oil (Diala-B). The experiment result shows that the tension penetrate of both oil are increase for increasing temperature, but lubricant oil SAE 40 have smaller increase than Diala-B. Keywords: lubricant oil, temperature, tension penetrate.